Peningkatan Kinerja Keuangan Institusi Wakaf di Indonesia: Landasan Hukum, Pengawasan Hukum, Pengelolaan Nadzir, Manajemen Resiko, Kepatuhan Syariah - Muhammad Iskandar; Dismane; Nugraha; Mayasari (Coopetition : Jurnal Ilmiah Manajemen, 2020)
This article analyzes the effectiveness and efficiency of the financial performance of waqf institutions in Indonesia in relation to legal foundations, supervision, nadzir governance, risk management and shari'ah compliance. This research was conducted in waqf institutions with a population and samples were obtained from 102 waqf institutions, each of which had 3 (three) nazirs who filled out the questionnaire for this study. The data were analyzed using descriptive and verification analysis as well as partial least square structural equation modeling. In general, the results of this study indicate that the effectiveness and efficiency of the financial performance of waqf institutions in Indonesia is influenced by legal foundations, supervision, nadzir governance, risk management and shari'ah compliance.